Testing Various Doses of Liquid Organic Fertilizer (LOF) on te Growth of Scallion (Allium fistulosum L.) - Novianto Novianto; Wartono Wartono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Scallion is one type of vegetable plant that is widely used as a flavouring or seasoning for dishes and other vegetable mixtures in several types of cuisine in Indonesia.  For this reason, one of the efforts that can be made to increase the production of scallions in meeting the consumption needs of the community is by means of technical cultivation through the application of liquid organic fertiliser (LOF).  The purpose of this study was to analyse the need for the right dose of LOF for scallions. This study used a non-factorial Randomised Group Design method by testing 6 treatment of LOF dose, namely: J1 = 1 ml/L water, J2 = 1.5 ml/L, J3 = 2 ml/L, J4 = 2.5 ml/L, J5 = 3 ml/L and J6 = 3.5 ml/L. Each treatment was repeated as many as 4 replications. The results from analysis of variance (ANOVA) showed that doses of LOF affected very significantly on the parameters of root length, root weight, wet stalk weight, and fresh shoot yield with the LOF dose of 1.5 ml/L water (J2) giving the best results. Keywords: Dosage, LOF, Root length, Shoot weight, Vegetable